2020
DOI: 10.21462/ijefl.v5i1.237
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal Framework in Analyzing Learners’ Attitudinal Resources on Performing Of Mice and Men

Abstract: This paper is carried out to find out the attitudinal resources used by students in Play Performance class through appraisal framework (Martin & White, 2005). It focuses on how the students negotiate attitudes to express their feelings, judgements, and appreciation of “Of Mice and Men” production process. The data for this qualitative study were collected from students’ reflections which were selected purposely from different production and artistic divisions. It analyses 109 expressions based on three dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…However, the limited use of affect by the translator suggests the TT does not fully capture the positive feelings described in the ST's expressive speech. This diverges from research by Zain and Nababan (2023)and Pasaribu (2020) that found more affect realizations when translating from English to Bahasa. The finding of the research makes the translator overlooked the underlying emotional and psychological experiences of the characters, failing to transfer the ST's emotional context into the TT.…”
Section: Discussion Attitude Sub-systemcontrasting
confidence: 99%
“…However, the limited use of affect by the translator suggests the TT does not fully capture the positive feelings described in the ST's expressive speech. This diverges from research by Zain and Nababan (2023)and Pasaribu (2020) that found more affect realizations when translating from English to Bahasa. The finding of the research makes the translator overlooked the underlying emotional and psychological experiences of the characters, failing to transfer the ST's emotional context into the TT.…”
Section: Discussion Attitude Sub-systemcontrasting
confidence: 99%
“…In addition, most of the previous research using theoretical appraisal focused on news text, writing, leader's speech, teacher talk, articles, etc. (e.g., (Chalimah et al, 2018) utilized it to Evaluating Attitudes in News Text; (Pribady, 2018) Used the Appraisal theory of the Teacher's Talk to Enhance Students' Critical Thinking Skills through Narrative Text; (Pasaribu, 2020) used this theory to analyze on Performing Of Mice and Men; (Rahayu et al, 2020) focus on analyzing the dominant type of attitudinal system that expressed by the teacher; (Haristyanti, 2015) used it to analyze Obama's speech. This research conducted through appraisal theory to analyze how students talk and teachers talk on online classroom interactions during the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%
“…All these negative evaluations build a reflection that The United States wants to tarnish the image of China and destroy the relationship between China and North Korea by its political news discourse. Pasaribu (2020) evaluates the attitudinal resources used by students in the Play Performance class entitled "Mice and Men" through an appraisal framework (Martin & White, 2005). The findings show that although students experience a certain degree of insecurity [-security], they reveal a positive inclination [+inclination] towards the production process.…”
Section: Introductionmentioning
confidence: 99%